Storytelling Digital Kisah Nabi sebagai Kolaborasi Modern Guru PIAUD dan PAI - Harefa, Jefriansyah; Sahyan, Sahyan (Prodi PIAUD STAI Sumatera Medan, 2025)
This study aims to explore the experiences of PIAUD and PAI teachers at RA Islamic Center in using digital storytelling as a collaborative medium for delivering stories of the Prophets to young children. Emerging from the need to present story-based instruction in a more engaging and relevant way in the digital era, this research reveals the dynamics of teacher collaboration in integrating pedagogical expertise and religious understanding through animated videos, narrated audio, and digital illustrations. Using a phenomenological approach, the study investigates teachers’ subjective experiences through in-depth interviews, classroom observations, and document analysis. The findings show that digital storytelling provides transformative technical, pedagogical, and religious experiences for teachers. Digital media helps visualize stories more concretely, strengthens narrative structure, and facilitates the internalization of moral values. In addition, collaboration between PIAUD and PAI teachers shapes a more integrative process of planning and value interpretation. For children, the use of digital media enhances engagement, memory retention, moral comprehension, and emotional responses to the figures of the Prophets. The study also emphasizes that digital storytelling is not merely a technical innovation but a modern pedagogical model that connects Islamic spirituality with narrative technology aligned with the world of young learners today.